The influence of transformational leadership, career development, and Organizational Citizenship Behavior on employee performance - Andita Sulistyowati; Amalina Nur Arifah (International Journal of Applied Finance and Business Studies, 2023)
Research conducted aims to analyze the influence of transformational leadership styles, career development, and Organizational Citizenship Behavior (OCB) on employee performance. The method used was a survey with a saturated sample, in which all 120 Pandatex employees were included in the study. A Likert scale questionnaire is used to collect primary data. Data analysis includes validity and reliability testing, as well as testing hypotheses through statistical methods. Research results show that transformational leadership styles have a positive impact on employee performance by motivating and encouraging them to go beyond expectations. Career development also has a significant impact on employee performance, by offering a wide range of careers, which in turn increases motivation and productivity. Furthermore, OCB has proved to be an important factor that improves organizational efficiency and employee performance. This research confirms the importance of factors such as Herzberg's motivational hygiene in boosting employee performance. From this research, companies can consider applying transformational leadership models, supporting career development, and driving OCB as a strategy to improve employee performance.